Correlating Thompson score and cardiac dysfunction in neonates suffering from perinatal asphyxia – A prospective observational study - Anushka Nag,; Bhaswati Ghoshal,; Meghna Siddhanta, (Asian Journal of Medical Sciences, 2024)
Background: Perinatal asphyxia continues to be a leading cause of neonatal morbidity and mortality worldwide. It causes multiorgan failure with brain involvement as the major organ of concern (hypoxic-ischemic encephalopathy). Cardiac dysfunction is also a feature of perinatal asphyxia. Aims and Objectives: The study and to correlate cardiac dysfunction detected by cardiac biomarkers and echocardiography with the severity of perinatal asphyxia as graded by the Thompson score. Materials and Methods: In this prospective observational study, babies with Apgar score <7 at 1 min received in the sick newborn care unit of a tertiary care hospital in West Bengal, India, were enrolled over 6 months. Thompson’s score was assessed on the 1st day with the estimation of creatine phosphokinase MB (CPK-MB) and troponin (Trn) T within 24 h of birth. Thompson score assessment was continued twice daily till discharge or death. Transthoracic echocardiography was done at the earliest within the 1st week. Results: Of the 81 neonates enrolled, 28 neonates had cardiac dysfunction detected by positive Trn T and raised CPK-MB. Echocardiography showed 15 neonates (18.5%) had systolic dysfunction whereas 13 (16.0%) had tricuspid regurgitation. There was a strong association between Thompson score and Trn T and CPK-MB (rpb=0.85, rho=0.97, respectively, P≤0.001). Thompson score was highly sensitive and specific in detecting the need for mechanical ventilation, and fluid restriction in inotrope-resistant cardiac dysfunction (sensitivity 90%, 78.4%, respectively; and specificity 95.8%, 97.7%, respectively), in predicting initiation of feeding and final outcome (sensitivity 82.9% and 100%, respectively, specificity 97.8%, 89%, respectively). Conclusion: Clinical assessment by the Thompson score can predict the degree of cardiac dysfunction, mechanical ventilation requirement, feed initiation, and final outcome in perinatal asphyxia.